TOLERANCE OF DIFFERENT RICE GENOTYPES (ORYZA SATIVA L.) AGAINST THE INFESTATION OF RICE STEM BORERS UNDER NATURAL FIELD CONDITIONS - Sarwar, M.; Ahmad, N.; Rullah, Nas; Tofique, M. (The Nucleus, 2010)
The present studies report the genotypic responses of 61 rice (Oryza sativa L.) genotypes (35 aromatic and 26 non aromatic) against the infestation of rice stem borers under natural field conditions. The data obtained on these genotypes on larval infestation in combination with yield were the criteria to assess the resistance depicted by them. The studies showed that among aromatic genotypes, ‘Khushboo-95’ gave the best yield of grain and harboured the least pest infestation (2.81% deadhearts and 1.85% whiteheads); on the other hand variety ‘Sonahri Sugdasi (P)’ harboured the highest borers attack (10.37% and 19.30%) and yielded the lowest grain yield. Regarding non-aromatic genotypes, IR8-2.5-11 received least infestation (1.32% and 0.26% deadhearts and whiteheads, respectively) generating highest yield showing its tolerance to borer’s attack, in contrast, genotype IR6-252 harboured the highest infestation (5.65%, 4.28%) and yielded minimum grain indicating its susceptibility. These results demonstrate the expression of resistance gene in the genome of tolerant rice genotypes that can provide season-long protection from the natural infestation of insect pests.